Presupposition in the Lyrics of ‘Erika’: A Pragmatic Study of Assumptions in a Controversial Context - Mesya Natalia Siboro; Giana Natasha Darosi Br. Sitepu; Suryani Praysiska Silalahi; Salwa Naysila; Rohmayani Kesogihen; Dian Marisha Putri (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
The presupposition in the lyrics of Erika song was analyzed by applying fairy tale theory of presupposition from George Yule, a pragmatic. This research attempts to analyze the species of presupposition in the song and also describe how implicit assumptions impact audience interpretation and public controversy. Qualitative descriptive is used in this study because the implicit meaning of lyrics tells by song. Data Source Lyrics of “Erika” or “Goyang Erika, Cinta 25 Karat” Orkes semi dangdut (OSD) Himpunan Mahasiswa Tambang (HMT) Institut Teknologi Bandung (ITB). Data were collected by documentation and library research methods. The analysis exposes two forms of presupposition, namely, existential and lexical presupposition. The first presupposition is existential presupposition which dominates as in the lyrics “Walau sudah janda” that implies having been married before, whereas Lexical Presuppositions can be found in this lyric. Their findings suggest that implicit stereotypes about women, sexuality, and gender shown in the lyrics also shape people views of the song beyond its literal meaning.